THE REGULATION OF THE CHEMICAL WEAPON USED THAT RELATED WITH SELF-DEFENSE ARRANGEMENT IN ARTICLE 51 OF THE UNITED NATIONS CHARTER - Rizka Faradilla; Adwani Adwani (Student Journal of International Law, 2022)
This study aims to find out about the regulation and the use of chemical weapons as a state's self-defense and to find out and explain the reasons why some countries use chemical weapons to defend themselves from attacks by other countries. This research is normative legal research, from the results of the study it was found that Article 51 of the United Nations Charter which regulates self-defense does not specifically explain the use of permissible weapons in self-defense so in practice there are still many countries that use chemical weapons despite their use forbidden in war. The United Nations should make changes to the contents of the United Nations Charter, especially in Article 51 on Self-defense in order to add more detailed rules regarding anticipatory actions for Self-defense so that no country admits to carrying out armed attacks with the aim of self-defense for their respective interests and harming many parties.